x(t) = -u(t-3)+2u​(t+1)-2u(t​-1)+u(t-3)

24 visualizaciones (últimos 30 días)
cadburry oreo
cadburry oreo el 4 de Oct. de 2020
Respondida: Jonas el 8 de Feb. de 2023
x(t) = -u(t-3)+2u(t+1)-2u(t-1)+u(t-3)
how to solve it ? help i'm new

Respuestas (1)

Jonas
Jonas el 8 de Feb. de 2023
please check your given equation, the last and first term cancel out each other. Nevertheless, i kept both of them in the code below
generate a time vector from -5 to 5 with step 0.1
t=-5:0.1:5;
generate unit step data
x=zeros(size(t));
preFactors=[-1 +2 -2 +1];
timeShifts=[-3 +1 -1 -3];
for termNr=1:numel(preFactors)
% create current unit impulse
thisTerm=t>-timeShifts(termNr);
% add up
x=x+preFactors(termNr)*thisTerm;
end
stem(t,x,'.')

Categorías

Más información sobre Systems of Nonlinear Equations en Help Center y File Exchange.

Etiquetas

Community Treasure Hunt

Find the treasures in MATLAB Central and discover how the community can help you!

Start Hunting!

Translated by